Investigating the anatomy of supplier selection in green public procurement. (1st December 2015) - Igarashi, Mieko; de Boer, Luitzen; Michelsen, Ottar
Abstract: Including environmental criteria in the supplier selection process complicates the decision-making of purchasers. The increasing pressure on purchasers to include environmental criteria raises the question how purchasers deal with this challenge. This paper assesses the inclusion of environmental criteria in supplier selection in the Norwegian public sector by identifying environmental criteria in official tender documents related to 41 purchases and analysing them both in a quantitative and qualitative way. The documents show that purchasers use different types of environmental criteria and that such criteria may be used in different stages of the selection process. Viewing our findings in the light of theories about behavioural decision-making, purchasers basically use four approaches for simplifying the green supplier selection problem: ignore, incorporate, insist and integrate. Typically, they avoid a direct trade-off between green performance and other classical purchasing criteria ('integrate'). It seems to be more common for purchasers to ignore environmental criteria, define them as part of other existing criteria ('incorporate'), or use them as qualifiers early in the selection process ('insist'). Policy-makers should develop policies that take into account the purchasers' four approaches. Practitioners should acknowledge these approaches to green supplier selection. This study contributes to the supplier selection literature by conceptualizing the inclusion of environmental criteria using two different decision-making paradigms and developing theoretical propositions as to how purchasers deal with the complexity of green supplier selection. Highlights: By assessing public tender documents, the use of green criteria was analyzed. Four strategies for using green criteria in supplier selection were identified. Purchasers typically avoid a trade-off between green and conventional criteria. Often, green criteria are used as qualifiers or embedded in conventional criteria.